If it's not what You are looking for type in the equation solver your own equation and let us solve it.
=Y+6(-5.11)
We move all terms to the left:
-(Y+6(-5.11))=0
We calculate terms in parentheses: -(Y+6(-5.11)), so:We get rid of parentheses
Y+6(-5.11)
We add all the numbers together, and all the variables
Y-30.66
Back to the equation:
-(Y-30.66)
-Y+30.66=0
We add all the numbers together, and all the variables
-1Y+30.66=0
We move all terms containing Y to the left, all other terms to the right
-Y=-30.66
Y=-30.66/-1
Y=30+0.66/1
| x+(x*1.1)=1.1 | | (3x)4=320 | | 2/5-2+4x=-3/5+-12 | | 19y-12y=7 | | x-7+2(5x+6)=-3(x+1) | | 4x+17=8x-11 | | 4(5x+2)=-5(4x-5)+2x | | 2m-4=4m | | -9a+25+6a=-3a-20 | | 7p-3=10p-15 | | 32/x+3=7/6 | | 6u+3-24=15u= | | -6k+2=9 | | 6u+3-24=15 | | 3x+x+x+x-3-2=7+7+x+x= | | 3z+17=35 | | 8p-3=50+6 | | 6a-22=-4(1+6a) | | 125c-0.45c=3,200 | | 3(4x+1)=-4(4x-1)-3x | | 4p-8=6p+4 | | 32/x+3=-8/3 | | 13r-8=11r+8 | | 4(x+2)+2=2(x-1)+16 | | (5x+7)=(8x−26) | | 13r-8=11+8 | | 4(4x+5)=-5(5x-5) | | 343=49^x+5 | | 4(4x+5)=-5(5x-5 | | ((202)/(4.5x-22.5))=0 | | 202/(4.5x-22.5)=0 | | 3r-20=2r-17 |